Effects of changes in the unemployment insurance eligibility requirements on job duration - Swedish evidence - Pathric Hägglund (Institute for Labour Market Policy Evaluation (IFAU), 2000)
This paper investigates the impact of the unemployment insurance (UI) entrance requirement on employment duration in Sweden. I study employment spells in 1992, 1996, and 1998 to find behavioural adjustments in the timing of job separation. The results suggest that some adjustments have occured. Comparisons between years with different UI requirements support the conclusion. By using predicted hazard rates for each week, I calculate an approximate 3-week extension in the average duration of employment spells between 1996 and 1998.
Keywords: J22; J65; J68; 330; Employment duration; Unemployment insurance